2016
DOI: 10.1002/bit.26086
|View full text |Cite
|
Sign up to set email alerts
|

MAR‐Mediated transgene integration into permissive chromatin and increased expression by recombination pathway engineering

Abstract: Untargeted plasmid integration into mammalian cell genomes remains a poorly understood and inefficient process. The formation of plasmid concatemers and their genomic integration has been ascribed either to non‐homologous end‐joining (NHEJ) or homologous recombination (HR) DNA repair pathways. However, a direct involvement of these pathways has remained unclear. Here, we show that the silencing of many HR factors enhanced plasmid concatemer formation and stable expression of the gene of interest in Chinese ham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
2
18
0
Order By: Relevance
“…C‐NHEJ typically leads to small insertion and deletions, whereas alternative end‐joining (alt‐EJ) repair activities relying on microhomologies at the DSB site to anneal broken ends often results in larger and more complex mutations. Although alt‐EJ repair is considered to be a backup pathway in most mammalian cells, we detected between 25% and 55% alt‐EJ compatible junctions when targeting the gag gene, supporting our previous conclusions of intrinsically elevated alt‐EJ activities in CHO cells (Bosshard, Duroy, & Mermod, ; Kostyrko & Mermod, ; Kostyrko et al, ). Interestingly, approximately 10% of all analyzed repair junctions contained insertions templated from other ERV loci, or from the same ERV locus but using a distant sequence, while others manifested apparent duplications devoid of microhomologies, as required by alt‐EJ mechanisms.…”
Section: Resultssupporting
confidence: 90%
“…C‐NHEJ typically leads to small insertion and deletions, whereas alternative end‐joining (alt‐EJ) repair activities relying on microhomologies at the DSB site to anneal broken ends often results in larger and more complex mutations. Although alt‐EJ repair is considered to be a backup pathway in most mammalian cells, we detected between 25% and 55% alt‐EJ compatible junctions when targeting the gag gene, supporting our previous conclusions of intrinsically elevated alt‐EJ activities in CHO cells (Bosshard, Duroy, & Mermod, ; Kostyrko & Mermod, ; Kostyrko et al, ). Interestingly, approximately 10% of all analyzed repair junctions contained insertions templated from other ERV loci, or from the same ERV locus but using a distant sequence, while others manifested apparent duplications devoid of microhomologies, as required by alt‐EJ mechanisms.…”
Section: Resultssupporting
confidence: 90%
“…Matrix attachment regions can increase expression levels of the transgene in stably transfected CHO cells [6][7][8][9][10][11][12]. However, the characteristics and mechanism of MARs function have not been elucidated, and further studies are needed to develop improved methods for transgene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gene copy numbers are related to transgene expression , and the methylation of DNA may reduce transgene expression . Some reports have demonstrated that MARs improve the expression of transgenes through the recombination pathway of synthesis‐dependent microhomology‐mediated end‐joining (MMEJ) . However, none of these studies assessed the effects of the characteristic sequences of MARs on transgene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the resulting productivity may vary, as it was shown that adjacent chromatin states can spread into newly integrated sequences. To avoid this, genetic sequences that maintain an open chromatin configuration have been used [195,196]. Direct silencing of the CMV promoter used for most transgenes, either by DNA-methylation or by changes in the histone modifications has also been shown [197][198][199][200].…”
Section: Maintaining Stabilitymentioning
confidence: 99%